Ice‐flow structure and ice dynamic changes in the Weddell Sea sector of West Antarctica from radar‐imaged internal layering. Issue 4 (3rd April 2015) - Bingham, Robert G.; Rippin, David M.; Karlsson, Nanna B.; Corr, Hugh F. J.; Ferraccioli, Fausto; Jordan, Tom A.; Le Brocq, Anne M.; Rose, Kathryn C.; Ross, Neil; Siegert, Martin J.
Abstract Recent studies have aroused concerns over the potential for ice draining the Weddell Sea sector of West Antarctica to figure more prominently in sea level contributions should buttressing from the Filchner‐Ronne Ice Shelf diminish. To improve understanding of how ice stream dynamics there evolved through the Holocene, we interrogate radio echo sounding (RES) data from across the catchments of Institute and Möller Ice Streams (IIS and MIS), focusing especially on the use of internal layering to investigate ice‐flow change. As an important component of this work, we investigate the influence that the orientation of the RES acquisition track with respect to ice flow exerts on internal layering and find that this influence is minimal unless a RES flight track parallels ice flow. We also investigate potential changes to internal layering characteristics with depth to search for important temporal transitions in ice‐flow regime. Our findings suggest that ice in northern IIS, draining the Ellsworth Subglacial Highlands, has retained its present ice‐flow configuration throughout the Holocene. This contrasts with less topographically constrained ice in southern IIS and much of MIS, whose internal layering evinces spatial changes to the configuration of ice flow over the past 10, 000 years. Our findings confirm Siegert et al.'s (2013) inference that fast flow was diverted from Bungenstock Ice Rise during the Late Holocene and suggest that this may have represented just one component of wider regional changes to ice flow occurring across the IIS and MIS catchments as the West Antarctic Ice Sheet has thinned since the Last Glacial Maximum.